Price and volume distributions in international equity markets - Lynch, Margaret (Trinity College (Dublin, Ireland). Trinity Business School, 2009)
This thesis examines asymmetry in international equity market returns, in associated trading volume distributions and in returns to funds of hedge funds. The method used in all three of the four empirical chapters is non-parametric, comprising three distribution-free tests, namely the Wilcoxon rank sum, the Siegel-Tukey and the binomial distribution. I conducted an original Monte Carlo study of the small sample behaviour of two distribution free tests, the Wilcoxon rank sum and the binomial distribution test. In the fourth empirical chapter I investigated the relationship between returns and volumes in 11 international equity markets using panel regressions and VAR models. I used a detrending technique involving the regression of logged volume on a time trend to counteract the well known positive drift associated with trading volumes distributions. In the econometric analysis I used variance decompositions to estimate the ordering of the variables in the VAR. In my impulse response analysis I used the generalised impulse response technique of Pesaran and Shin (1999).
Keywords: Business, Ph.D.; Ph.D. Trinity College Dublin.